A wideband integrated piezoelectric bistable generator: Experimental performance evaluation and potential for real environmental vibrations. (May 2015) - Liu, Weiqun; Badel, Adrien; Formosa, Fabien; Wu, Yipeng; Bencheikh, Nabil; Agbossou, Amen
Bistable generators have been proposed as potential solutions to the challenge of variable vibration frequencies. This article presents a novel mono-block design of bistable generator based on mechanical buckling effect. A bistable structure composed of four thin beams as flexible hinges, two amplified piezoelectric stacks as electromechanical springs, and a dynamic mass is fabricated. Its volume is 5.46 cm 3, and it reaches a power density of 0.48 mW/cm 3 . The wideband and high-power energy harvesting properties are first validated using chirp excitations with an obtained bandwidth of 11 Hz (812% improvement compared with the linear equivalent case). The generator's good performance is then further confirmed for bandlimited noise excitations and a real vibration signal from a driving car wheel.